Colour polymorphism and protective coloration in coconut crabs. Issue 6 (2nd November 2019) - Caro, Tim; Cluff, Emma; Morgan, Victoria M.
Abstract : Phenotypic colour polymorphisms are common in nature but their adaptive significance is often difficult to interpret. Terrestrial coconut crabs Birgus latro have cohabiting distinct red and blue colour morphs and earlier research suggested that red morphs are more cryptic in open inland areas whereas blue morphs are more cryptic in nearshore closed environments, hinting that microhabitat specialization maintains the polymorphism. We used five independent methods to investigate this hypothesis. (i) Behavioural observations of crabs in the wild, and (ii) behaviour of wild-caught crabs exploring an arena revealed no differences in habitat-specific movement patterns between morphs. (iii) An experiment with red and blue plasticine covered model crabs placed out in the field uncovered no consistent differences in visitation rates by terrestrial hermit crabs or live coconut crabs based on the colour of the plasticine. (iv) An experiment involving people locating model crabs in the field generated inconclusive evidence that one morph was more cryptic than the other. (v) An updated large dataset comprising over 500 live crabs found that neither morph showed a preference for one habitat with different degrees of exposure. Our findings lend no support to the idea that red and blue crabs preferentially occupy different habitats to gain protective advantages, or that coloration influences visits by people or sympatric species, or that morphs behave differently in relation to habitat exposure. Colour polymorphism in this species is unlikely to be maintained by niche-specific protective coloration, and may be a neutral polymorphism although this requires investigation.